UPAYA GURU DALAM MENINGKATKAN AKTIVITAS BELAJAR IPS PADA KELAS VIII SMPN 2 TELEN - Risnawati, Risnawati; Reza, Reza; Ellyawati, Noor (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The research in this thesis is motivated by the low level of student learning activity in Social Sciences subjects. Therefore, the focus of research in this thesis is how teachers make efforts to improve learning activities. This research also aims to find out what efforts teachers have made to improve social studies learning activities in class VIII at SMPN 2 Telen. The type of research carried out was descriptive qualitative. The informants in this research were social studies teachers. Data collection was carried out by direct observation and interviewing social studies subject teachers. Based on the research results, it was concluded that the teacher's efforts to increase social studies learning activities in class VIII SMPN 2 Telen are reflected in his efforts as follows: (1) The teacher attracts students' attention, (2) The teacher motivates students before explaining the lesson material, (3) The teacher encourages students to be active during the learning process, (4) The teacher explains the basic competencies of the material to be discussed, (5) The teacher explains the objectives that must be achieved from the material being studied, (6) The teacher explains the competencies that students must have before starting the lesson , (7) The teacher provides an overview of the material that will be discussed, (8) The teacher tells students easy ways to understand the material, (9) The teacher uses interesting learning methods, (10) The teacher uses learning media according to the material being studied, ( 11) The teacher diligently asks students about the material studied, (12) The teacher responds to questions asked by his students, (13) The teacher conducts an evaluation at the end of the lesson and (14) The teacher concludes the lesson material. The efforts made by teachers to increase social studies learning activities for class VIII students are categorized as